2017
DOI: 10.4238/gmr16019637
|View full text |Cite
|
Sign up to set email alerts
|

SHORT-COMMUNICATION Evaluation of perfused bovine udder for gene expression studies in dairy cows

Abstract: ABSTRACT. Intramammary infections are one of the main causes of productivity loss in dairy cows. To better understand the immune system response and to avoid the use of live animals, we validated the use of isolated bovine udder as an ex situ model. Six mammary glands were collected from cows ready for culling. Three udders were perfused with Tyrode's solution and three were not-perfused. During six hours, we collected perfusate samples for biochemical analysis. We also collected alveolar and teat canal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The viability of the perfused udders was controlled using biochemical parameters such as lactate dehydrogenase (LDH)-activity, glucose consumption and lactate production in the perfusate (Ehinger and Kietzmann, 2000). Perfusate was sampled at 0 and 3 h post-inoculation (hpi) with S. agalactiae and indicated that the perfused bovine udders were viable throughout the experiment as reported by our research group before (Pinto et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viability of the perfused udders was controlled using biochemical parameters such as lactate dehydrogenase (LDH)-activity, glucose consumption and lactate production in the perfusate (Ehinger and Kietzmann, 2000). Perfusate was sampled at 0 and 3 h post-inoculation (hpi) with S. agalactiae and indicated that the perfused bovine udders were viable throughout the experiment as reported by our research group before (Pinto et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…An ethical and practical issue about the use of in vivo models represents an important limitation in animal studies and the ex-vivo or extracorporeal model approach is a potentially useful alternative. This isolated perfused bovine udder approach has been reported to be suitable in studies of mammary gland metabolism (Hardwick and Linzell, 1960) and pharmacokinetics of substances after intramammary administration (Kietzmann et al ., 1993, 2010) and recently to evaluate gene expression (Pinto et al ., 2017). However, this method has not been widely used to evaluate the transcriptional response of mammary gland against pathogens.…”
mentioning
confidence: 99%
“…However, increasing concern for animal welfare is increasing the community pressure on ethics committees for animal use in experiments. As a result, ethics committees have recommended stricter protocols and the reduction or, if possible, the replacement of animals with alternative laboratory methods (Hartung, 2008; Pinto et al ., 2017). In addition, experiment length and the costs to the acquisition of animals, feeding and labour are important limitations of in vivo procedures (Doke and Dhawale, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…When rst experiments in udders were accomplished, study results of ex vivo infection experiments in isolated perfused udders have been published that support the feasibility to use udders as a meaningful model [18,19]. Nevertheless, we believe that the current data are still valuable, as the LPS stimulation allows a direct comparison with former in vitro and in vivo studies and helps to further evaluate the values of isolated perfused bovine udders in mastitis research.…”
Section: Discussionmentioning
confidence: 82%